Boosting Classroom Interaction Based on Higher Order Thinking Skills (HOTS) in English Learning for Beginners - Syafryadin, Syafryadin; Harahap, Alamsyah; Haryani, Haryani; Astrid, Annisa (International Journal of Language Education, 2021)
Asking activity is a form of class interaction that needs attention. With the asking activity, it can increase the questioner’s knowledge. This study aimed to identify the questions form that filed by teachers and students in the classroom following the framework of thinking mandated in the revised Bloom Taxonomy and to explore the problems faced by lecturers in implementing the HOTS-based learning process. This study used qualitative methods by applying observation sheets and interview to collect data. The data analysis of this research used analysis of domain, taxonomy, component, and theme. The results of this study indicate that lecturers and students have applied the principles of Higher Order Thinking Skills (HOTS) from core learning activities to final learning activities. The form of the question is in level C4 (Analyzing), C5 (Evaluating), and C6 (Creating), but in the form of Creating questions, students still need to increase the frequency in asking. The problem faced is the difficulty in stimulating students who can answer and ask questions at level C6 in HOTS. Therefore, lecturers also try to overcome these problems by implementing strategies in the learning process.